Constructing and Crossing Boundaries in a New (?) Europe - Nagy, Erika (European Spatial Research and Policy, 2010)
During the last two decades, discourses over the transition process shifted toward a theoretical diversity and a deeper understanding of ‘how modernity was reworked in postsocialist context’. It was widely argued that changing social relations were shaped not only by norms and institutions of Neoliberal capitalism, but also by established networks, institutional and regulatory structures and actors that/who gave diverse responses to the profound and thorough transformation of the society. This paper aims at understanding how geopolitical discourses over the Balkan and its place in the ‘new Europe’ shaped social relations and produced daily practices nested into those webs, through the perception and interpretations of post-socialist transformation by Hungarian migrants who left the war-hit Yugoslavia.